HE4 as an Early Detection Biomarker of Epithelial Ovarian Cancer: Investigations in Prediagnostic Specimens From the Janus Serumbank. Issue 9 (1st November 2015) - Gislefoss, Randi Elin; Langseth, Hilde; Bolstad, Nils; Nustad, Kjell; Mørkrid, Lars
Abstract : Objectives: Epithelial ovarian cancer is characterized by nonspecific signs and clinical symptoms arising at late stages. Early detection is therefore important and may significantly improve the survival rate. Cancer antigen 125 (CA125) has been the most extensively studied serum biomarker in epithelial ovarian cancer, but low specificity limits its usefulness. A relatively novel biomarker, human epididymis protein 4 (HE4), has shown promise in early detection of the disease. The aim of this study was to investigate how early the tumor marker increases before diagnosis. Methods/Materials: A nested case-control design was used to evaluate the performance of HE4 and CA125 in prediagnostic serum samples from the Janus Serumbank. Serial specimens from 120 women with invasive epithelial ovarian cancer were compared with healthy controls. Serum level of CA125, HE4, and cotinine was measured. Spearman correlation and multiple linear regression analyses were used to investigate impact of smoking, age, storage time, and lag time (time from sampling until date of diagnosis). Results: Spearman correlation showed a strong positive correlation between HE4 and smoking in both cases and controls. Multiple linear regression analyses for pairwise differences between case and control showed that serum level of HE4 and CA125 was significantly increased ( P = 0.002 and P < 0.001, respectively) 2 years before diagnosis and that CA125 also was significantly increased up to 4 years before diagnosis ( P = 0.002). Conclusions: The present study showed that a difference between cases and controls in serum concentration of HE4 seemed to be increased 2 years before diagnosis and that CA125 was increased until 4 years before diagnosis.